2021
DOI: 10.24815/jaroe.v4i1.20252
|View full text |Cite
|
Sign up to set email alerts
|

Contractor Intention on Contractors’ All Risk Takaful Product in Malaysian Construction Industry

Abstract: Objective – Contractors’ All Risks (CAR) Takaful is completely different from CAR conventional insurance. CAR conventional insurance involves elements of usury (riba), gambling (maysir) and uncertainty (gharar) in their resources and operations which is prohibited by Shari’ah. This paper aims to investigate the relationship between attitude, awareness, understanding, religiosity, subjective norm, service quality and role of agents with contractor’s intention in choosing CAR Takaful products based on theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Most of the firms are relying on agents to sell their services. It has been observed that financial sectors have hired several agents who act as a mediator between the financial service firm and the customers (Ibrahim et al , 2021). Those committed to providing valuable services to their customers end up winning the trust of their potential target audience (Jap, 2001).…”
Section: Theoretical Background and Concept Developmentmentioning
confidence: 99%
“…Most of the firms are relying on agents to sell their services. It has been observed that financial sectors have hired several agents who act as a mediator between the financial service firm and the customers (Ibrahim et al , 2021). Those committed to providing valuable services to their customers end up winning the trust of their potential target audience (Jap, 2001).…”
Section: Theoretical Background and Concept Developmentmentioning
confidence: 99%
“…Kemudian, hasil penelitian ini sejalan dengan penelitian (Ibrahim et al, 2021) (A. Husin, 2016 (Kazaure, 2017) (Hassan, 2019) (Raza et al, 2019) (Bhatti, Tariq, 2020) bahwasanya sikap, subjective norm, dan perceived behavioral control memengaruhi minat seseorang untuk mengadopsi asuransi syariah. Selanjutnya, sikap dan perceived behavioral control menjadi variable yang paling memengaruhi minat untuk mengadopsi asuransi Syariah dengan nilai p-value sebesar 0.000 (p<0.01) dengan tingkat signifikansi pada level 1% (0.1).…”
Section: Perceived Behavioral Control Terhadap Minat Mengadopsi Asura...unclassified